2017
DOI: 10.17851/2237-2083.25.3.1367-1395
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral study to investigate the processing routes of grammatical gender in Brazilian Portuguese

Abstract: Este artigo apresenta um estudo comportamental que teve como objetivo investigar se substantivos inanimados do português do Brasil, transparentes quanto ao seu gênero gramatical (substantivos femininos terminados em -a e masculinos terminados em -o) e opacos (outras terminações) são ou não processados por mecanismos cognitivos distintos. Para tanto, uma tarefa de concordância de gênero foi executada por 19 sujeitos em duas condições: entre um artigo definido e um substantivo (condição 1) e entre um substantivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Regarding research question 3, an alternative view of the role of noun phonological cues was proposed based on the studies carried out with regular and irregular verbal morphology in English, the Dual Mechanism Model (Pinker 1990(Pinker , 1999. In line with previous studies testing this hypothesis on gender agreement in Portuguese (Resende and Mota 2017), the present investigation did not fully meet the predictions of the Dual Mechanism Model. The present investigation found that participants were faster with low-frequency transparent nouns than with low-frequency opaque nouns, in line with the predictions of the model.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Regarding research question 3, an alternative view of the role of noun phonological cues was proposed based on the studies carried out with regular and irregular verbal morphology in English, the Dual Mechanism Model (Pinker 1990(Pinker , 1999. In line with previous studies testing this hypothesis on gender agreement in Portuguese (Resende and Mota 2017), the present investigation did not fully meet the predictions of the Dual Mechanism Model. The present investigation found that participants were faster with low-frequency transparent nouns than with low-frequency opaque nouns, in line with the predictions of the model.…”
Section: Discussionmentioning
confidence: 54%
“…There is not much research that compares the processing patterns of regular and irregular verbal morphology with the patterns of irregular nominal endings in languages with nominal agreement. Resende and Mota (2017) studied these patterns testing the Dual Mechanism Model with transparent/ opaque and regular/irregular noun endings in monolingual speakers of Brazilian Portuguese. Investigators manipulated word frequency and gender marking cues (opaque/transparent and regular/irregular) in a timed gender selection task with determiner-noun and noun-adjectival agreement.…”
Section: Monolingual Speakersmentioning
confidence: 99%